Battery
By adding solid electrolyte to the edge coating structure of the electrode sheet, the material components of the electrode material layer and the edge coating structure are similar, and the problem of inconsistent reduction of the thickness of the electrolyte sheet and the electrode sheet in solid lithium batteries is solved, and the quality of the finished product is improved.
Patent Information
- Application Number
- CN202411845166.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the manufacturing process of solid-state lithium batteries, the sizes of the positive electrode sheet and the negative electrode sheet are inconsistent, resulting in inconsistent thickness reduction between the electrolyte sheet and the electrode sheet during the overlapping process, cracks or microcracks occur, affecting the quality of the finished product of the battery.
By adding solid electrolyte to the edge coating structure of the electrode sheet, the material components of the electrode material layer and the edge coating structure are as similar as possible, so as to maintain consistency in thickness reduction during the stacking process, and avoid cracking or microcracking of the electrolyte sheet and current collector.
It effectively avoids cracking or microcracks of the electrolyte sheet and current collector during the stacking process, and improves the finished product quality of the battery cell and battery.
Smart Images

Figure CN119650813A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a battery. Background Art
[0002] The battery cell of a solid-state lithium battery includes an electrode sheet and an electrolyte sheet. The electrode sheet includes a positive electrode sheet and a negative electrode sheet. The electrolyte sheet is arranged between the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive current collector and a positive electrode active material layer covered on the positive current collector. The negative electrode sheet includes a negative current collector and a negative electrode active material layer covered on the negative current collector. The electrolyte sheet is sandwiched between the positive electrode active material layer and the negative electrode active material layer for transmitting lithium ions. During the manufacturing process of the solid-state battery, it is necessary to add a pressure of 100 MPa to make the positive electrode sheet, the negative electrode sheet and the electrolyte sheet fit tightly. In the prior art, the sizes of the positive electrode sheet and the negative electrode sheet are usually inconsistent. For example, the size of the positive electrode active material layer is smaller than the size of the negative electrode sheet, or the size of the negative electrode active material layer is smaller than the size of the positive electrode sheet. The electrolyte sheet is usually adapted to the larger size of the positive electrode sheet to ensure that the energy of one of the positive electrode active material layer and the negative electrode active material can be fully utilized.
[0003] Specifically, an electrode material layer (a positive electrode active material layer or a negative electrode active material layer) is disposed on a current collector, the size of the electrode material layer is smaller than the size of the current collector, a side coating structure is disposed around the outer periphery of the electrode material layer, and the current collector, the electrode material layer and the side coating structure constitute an electrode sheet. An electrolyte sheet needs to be stacked on one side of the electrode material layer, and the edge area of the electrolyte sheet falls on the side coating structure.
[0004] In the prior art, the material components of the electrode material layer and the side coating structure are quite different. When pressure is applied to stack the electrolyte sheet and the electrode sheet, the thickness reduction of the electrode material layer and the side coating structure under the action of pressure is difficult to maintain consistency. The surface of the electrode material layer and the surface of the side coating structure are uneven, resulting in cracks or microcracks in the edge area of the electrolyte sheet and the edge area of the current collector, affecting the quality of the finished solid-state lithium battery. Summary of the invention
[0005] The purpose of the present application is to provide a battery, which can keep the thickness of the electrode material layer and the edge coating structure as consistent as possible during the process of stacking electrode sheets and electrolyte sheets, avoid cracking or microcracks in both the electrolyte sheet and the current collector, and improve the quality of the finished products of the battery cell and the battery.
[0006] To achieve this goal, this application adopts the following technical solutions:
[0007] A battery is provided, comprising at least one battery cell, wherein the battery cell comprises an electrode sheet and an electrolyte sheet, wherein the electrode sheet and the electrolyte sheet are stacked, and the electrode sheet comprises:
[0008] current collector;
[0009] An electrode material layer is disposed on the current collector and falls within the region where the current collector is located, and the outer contour of the region where the electrode material layer is located is at least partially spaced from the outer contour of the region where the current collector is located, so that a support region is formed between the outer contour of the region where the electrode material layer is located and the outer contour of the region where the current collector is located;
[0010] A side coating structure is provided in the support area; the electrolyte sheet covers at least a portion of the electrode material layer and at least a portion of the side coating structure;
[0011] The material components of the edge coating structure include a solid electrolyte.
[0012] As some embodiments of the battery provided in the present application, the material components of the electrode material layer include a solid electrolyte.
[0013] As some embodiments of the battery provided in the present application, the mass of the solid electrolyte in the electrode material layer accounts for a percentage of the total mass of the electrode material layer, and the mass of the solid electrolyte in the edge coating structure accounts for b percentage of the total mass of the edge coating structure;
[0014] The absolute value of the difference between a and b is greater than or equal to 0 and less than or equal to 5%.
[0015] As some embodiments of the battery provided in the present application, the mass of the solid electrolyte in the electrode material layer accounts for a percentage of the total mass of the electrode material layer, and a is greater than or equal to 5% and less than or equal to 35%.
[0016] As some embodiments of the battery provided in the present application, the mass of the solid electrolyte in the edge coating structure accounts for a percentage of b of the total mass of the edge coating structure; b is greater than or equal to 5% and less than or equal to 35%.
[0017] As some embodiments of the battery provided in the present application, the material components of the edge coating structure also include insulating oxides and adhesives.
[0018] In some embodiments of the battery provided in the present application, the mass of the insulating oxide in the edge coating structure accounts for a percentage of c of the total mass of the edge coating structure, and c is greater than or equal to 65% and less than or equal to 90%.
[0019] As some embodiments of the battery provided in the present application, the mass of the adhesive in the edge coating structure accounts for a percentage of d in the total mass of the edge coating structure; d is greater than or equal to 1% and less than or equal to 5%.
[0020] As some embodiments of the batteries provided in the present application, the insulating oxide includes any one of aluminum oxide, silicon oxide, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium oxide, aluminum oxide homologues, silicon oxide homologues, lithium aluminum titanium phosphate homologues, and lithium lanthanum zirconium oxide homologues, or a combination of at least two of them.
[0021] As some embodiments of the batteries provided in the present application, the adhesive includes any one of polyisobutylene, hydrogenated nitrile rubber, nitrile rubber, hydrogenated styrene-butadiene block copolymer, derivatives of polyisobutylene, derivatives of hydrogenated nitrile rubber, derivatives of nitrile rubber, and derivatives of hydrogenated styrene-butadiene block copolymer, or a combination of at least two of them.
[0022] As some embodiments of the battery provided in the present application, the type of the solid electrolyte in the edge coating structure is the same as the type of the solid electrolyte in the electrode material layer.
[0023] Beneficial effects of this application:
[0024] The present application provides a battery, since the material components of the side coating structure include solid electrolytes, and the material components of the electrode material layer also include solid electrolytes, so that the material components of the electrode material layer and the material components of the side coating structure are as similar as possible. In the process of stacking the electrolyte sheet and the electrode sheet, the thickness of the electrode material layer and the thickness of the side coating structure will gradually decrease under pressure. Since the material components of the electrode material layer and the material components of the side coating structure are similar, the thickness reduction degree of the electrode material layer and the side coating structure under pressure is almost the same, that is, after applying pressure to the electrode material layer and the side coating structure at each moment, the thickness of the electrode material layer and the thickness of the side coating structure are almost the same, the side of the electrode material layer facing the current collector and the side of the side coating structure facing the current collector are almost flush, and the side of the electrode material layer facing the electrolyte sheet and the side of the side coating structure facing the electrolyte sheet are almost flush, so that cracking or microcracks of the electrolyte sheet and the current collector can be avoided, and the quality of the finished products of the battery cell and the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0026] Figure 1 is a schematic diagram of an electrode material layer on a current collector provided in a specific embodiment of the present application;
[0027] Figure 2 is a side view of an electrode sheet provided in a specific embodiment of the present application;
[0028] Figure 3 It is a schematic diagram of the stacking of the electrode sheet and the electrolyte sheet provided in the specific embodiment of the present application;
[0029] Figure 4 is a schematic diagram of a positive electrode material layer on a positive electrode current collector provided in a specific embodiment of the present application;
[0030] Figure 5 It is a side view of one of the independent battery cells provided in the specific embodiment of the present application;
[0031] Figure 6 is a schematic diagram of a negative electrode material layer on a negative electrode current collector provided in a specific embodiment of the present application;
[0032] Figure 7 is a side view of another independent battery cell provided in a specific embodiment of the present application;
[0033] Figure 8 is an internal schematic diagram of a battery provided in a specific embodiment of the present application;
[0034] Fig. 9 It is an external schematic diagram of a battery provided in a specific embodiment of the present application.
[0035] In the figure:
[0036] 1. Current collector; 2. Electrode material layer; 3. Edge coating structure; 20. Support area;
[0037] 100, battery cell; 200, packaging structure; 300, connecting piece; 400, heat conducting layer; 500, positive electrode ear of battery; 600, negative electrode ear of battery;
[0038] 10. electrode sheet; 110. positive electrode sheet; 120. negative electrode sheet; 130. electrolyte sheet;
[0039] 111, positive electrode current collector; 112, positive electrode material layer; 1110, positive electrode ear;
[0040] 121. negative electrode current collector; 122. negative electrode material layer; 1210. negative electrode tab. DETAILED DESCRIPTION
[0041] The present application will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only the parts related to the present application, rather than all structures, are shown in the accompanying drawings.
[0042] In the description of this application, unless otherwise clearly specified and limited, the terms "connected", "connected", and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0043] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0044] In the description of this embodiment, the terms "upper", "lower", "left", "right" and other directions or positional relationships are based on the directions or positional relationships shown in the drawings, and are only for the convenience of description and simplified operation, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation of the present application. In addition, the terms "first" and "second" are only used to distinguish in the description and have no special meaning.
[0045] In this embodiment, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this application generally indicates that the associated objects before and after are in an "or" relationship.
[0046] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.
[0047] like Figure 1 , Figure 2 As shown, it is a schematic diagram of the electrode sheet 10 of the battery cell provided in the embodiment of the present application, as Figure 3As shown, it is a schematic diagram of the electrode sheet 10 and the electrolyte sheet 130 of the battery cell provided in an embodiment of the present application, and the electrode sheet 10 and the electrolyte sheet 130 are stacked. The electrode sheet 10 includes a current collector 1, an electrode material layer 2 and a side coating structure 3. The electrode material layer 2 is arranged on the current collector 1 and falls in the area where the current collector 1 is located. The outer contour of the area where the electrode material layer 2 is located is at least partially spaced from the outer contour of the area where the current collector 1 is located, so that a support area 20 is formed between the outer contour of the area where the electrode material layer 2 is located and the outer contour of the area where the current collector 1 is located; the side coating structure 3 is arranged in the support area 20. In the battery cell 100, the electrolyte sheet 130 covers at least a portion of the electrode material layer 2 and at least a portion of the side coating structure 3. Specifically, when the electrolyte sheet 130 is stacked on the side of the electrode material layer 2 facing away from the current collector 1, as shown in FIG. Figure 3 As shown, a portion of the electrolyte sheet 130 falls on the electrode material layer 2 , and another portion falls on the edge coating structure 3 .
[0048] After the electrolyte sheet 130 and the electrode sheet 10 are stacked, pressure is applied to the electrolyte sheet 130 and the electrode sheet 10. During the pressure application process, the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 will gradually decrease under the pressure. If the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 are greatly different during the pressure application process, the surface of the electrode material layer 2 and the side coating structure 3 facing the current collector 1 and the surface facing the electrolyte sheet 130 will be uneven, causing microcracks to form in the current collector 1 and the electrolyte sheet 130 during the stacking process. For example, microcracks may form in the edge areas of the current collector 1 and the electrolyte sheet 130. If cracks form in the edge area of the current collector 1, the effective contact area between the electrode material layer 2 and the current collector 1 may be reduced, thereby affecting the charge transfer efficiency. If cracks form in the edge area of the electrolyte sheet 130, the lithium ion transmission channel may be damaged, the lithium ion conduction efficiency may be reduced, the internal resistance of the battery may be increased, and the charge and discharge performance may be deteriorated.
[0049] In the embodiment of the present application, the difference between the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 is greater than or equal to 0 and less than or equal to 10 μm, so before pressure is applied to the electrode material layer 2 and the side coating structure 3, the thickness of the two is almost equal. After the electrolyte sheet 130 and the electrode sheet 10 are stacked, during the process of applying pressure to the electrolyte sheet 130 and the electrode sheet 10, the difference between the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 is small, which is conducive to avoiding microcracks on the current collector 1 and the electrolyte sheet 130.
[0050] In the embodiment of the present application, the material components of the electrode material layer 2 and the material components of the side coating structure 3 both include solid electrolytes, so that the material components of the electrode material layer 2 and the material components of the side coating structure 3 are as similar as possible. In the process of stacking the electrolyte sheet 130 and the electrode sheet 10, the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 will gradually decrease under pressure. Since the material components of the electrode material layer 2 and the material components of the side coating structure 3 are similar, the thickness reduction degree of the electrode material layer 2 and the side coating structure 3 under pressure is almost the same, that is, after applying pressure to the electrode material layer 2 and the side coating structure 3 at each moment, the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 are almost the same, the side of the electrode material layer 2 facing the current collector 1 and the side of the side coating structure 3 facing the current collector 1 are almost flush, and the side of the electrode material layer 2 facing the electrolyte sheet 130 and the side of the side coating structure 3 facing the electrolyte sheet 130 are almost flush, so that cracks or microcracks in the electrolyte sheet 130 and the current collector 1 can be avoided, and the quality of the finished products of the battery cell 100 and the battery is improved.
[0051] In some embodiments, the thickness of the electrode material layer 2 is equal to the thickness of the edge coating structure 3, that is, the difference between the two thicknesses is 0. When the electrolyte sheet 130 and the electrode sheet 10 are stacked, the thickness consistency of the electrode material layer 2 and the edge coating structure 3 can be improved.
[0052] In some embodiments, the thickness of the electrode material layer 2 and the thickness of the side coating structure 3 may be different, but the difference in thickness between the two is less than or equal to 10μm. Exemplarily, the difference in thickness between the electrode material layer 2 and the side coating structure 3 is 1μm, 1.3mm, 1.8mm, 2μm, 2.5mm, 3μm, 4μm, 4.7mm, 5μm, 5.3mm, 6μm, 6.5mm, 7μm, 8μm, 8.2mm, 9μm, and 10μm.
[0053] Assume that the electrode material layer 2 has N edges, where N is a positive integer greater than or equal to 3. For example, a rectangular electrode material layer 2 has four edges, and a pentagonal electrode material layer 2 has five edges. When the electrode material layer 2 is covered on the current collector 1, it is assumed that M edges of the electrode material layer 2 are flush with the edge of the current collector 1, 0≤M<N, and the remaining NM edges are spaced from the edge of the current collector 1. The area between the NM edges and the edge of the current collector 1 forms a support area 20, and the edge coating structure 3 is arranged in the support area 20.
[0054] In some embodiments, the edge intervals of the current collector 1 are arranged outside the edge of the electrode material layer 2, that is, the N edges of the electrode material layer 2 are arranged at intervals from the edge of the current collector 1, and the formed support area 20 is annular, and the edge coating structure 3 is arranged in the annular area, so that the edge coating structure 3 is arranged along the circumference of the electrode material layer 2.
[0055] For example, see Figure 1 and Figure 2 The electrode material layer 2 is rectangular and has four sides (N=4). Figure 1 There are gaps between the four edges of the electrode material layer 2 shown and the edges of the current collector 1, that is, the length dimension of the electrode material layer 2 is smaller than the length dimension of the current collector 1, and the width dimension of the electrode material layer 2 is smaller than the width dimension of the current collector 1, so that the support area 20 is an annular area. Correspondingly, the edge coating structure 3 is arranged around the electrode material layer 2. Alternatively, one edge of the electrode material layer 2 is flush with one edge of the current collector 1, and the other three edges are spaced from the edges of the current collector 1, in which case the edge coating structure 3 is arranged on one side of the three edges. Alternatively, there is a gap between only one edge or only two edges of the electrode material layer 2 and the edge of the current collector 1, in which case the edge coating structure 3 is arranged on one side of the one edge or the two edges.
[0056] In this embodiment, the mass percentage of the solid electrolyte in the electrode material layer 2 to the total mass of the electrode material layer 2 is set to a, and the mass percentage of the solid electrolyte in the edge coating structure 3 to the total mass of the edge coating structure 3 is set to b. For ease of description, the "mass percentage of the solid electrolyte in the electrode material layer 2 to the total mass of the electrode material layer 2" is referred to as the "mass percentage of the solid electrolyte in the electrode material layer 2", and the "mass percentage of the solid electrolyte in the edge coating structure 3 to the total mass of the edge coating structure 3" is referred to as the "mass percentage of the solid electrolyte in the edge coating structure 3".
[0057] Among them, the mass proportion a of the solid electrolyte in the electrode material layer 2 is greater than or equal to 5% and less than or equal to 35%, so that the electrode material layer 2 has a higher electrical conductivity, which is beneficial to reducing the internal resistance of the electrode sheet 10. Moreover, since the mass proportion of the solid electrolyte in the electrode material layer 2 is less than or equal to 35%, it will not occupy too much of the proportion of other material components in the electrode material layer 2.
[0058] Exemplarily, the mass proportion a of the solid electrolyte in the electrode material layer 2 is 5%, 7.5%, 10%, 12%, 12.8%, 15%, 20%, 22.4%, 25%, 27%, 30%, 33.6%, 35%, etc.
[0059] Furthermore, the mass proportion b of the solid electrolyte in the edge coating structure 3 is greater than or equal to 5% and less than or equal to 35%. That is, the value range of b is the same as the value range of a, so that the mass proportion of the solid electrolyte in the edge coating structure 3 is similar to the mass proportion of the solid electrolyte in the electrode material layer 2, thereby improving the similarity of the material components of the two.
[0060] Optionally, the absolute value of the difference between a and b is greater than or equal to 0 and less than or equal to 5%.
[0061] In some embodiments, a and b can be equal (i.e., the difference between a and b is equal to 0), so that the mass proportion of the solid electrolyte in the edge coating structure 3 and the electrode material layer 2 is consistent, thereby making the material components of the two more similar. In the process of stacking the electrolyte sheet 130 and the electrode sheet 10, it helps to improve the consistency of the thickness change of the edge coating structure 3 and the electrode material layer 2, thereby better preventing the electrolyte sheet 130 and the current collector 1 from cracking.
[0062] Exemplarily, a and b are 5%, 7.5%, 9.2%, 10%, 12.5%, 15%, 16.8%, 17.5%, 20%, 22.5%, 24%, 25%, 27.5%, 30%, 31.4%, 32.5%, 33%, 35%, etc.
[0063] In other embodiments, a and b may also be unequal, but the absolute value of the difference between a and b is less than or equal to 5%, so that the mass proportion of the solid electrolyte in the edge coating structure 3 and the electrode material layer 2 is as close as possible, thereby improving the similarity of the material components of the edge coating structure 3 and the electrode material layer 2, and thus reducing the possibility of cracking on the electrolyte sheet 130 and the current collector 1 during the process of stacking the electrolyte sheet 130 and the electrode sheet 10.
[0064] For example, the absolute value of the difference between a and b can be 0.5%, 1%, 1.2%, 1.5%, 2%, 2.3%, 2.5%, 3%, 3.5%, 3.8%, 4%, 4.5%, 4.6%, 5%. For example, a is 10%, b is 12.5%, and the difference between the two is 2.5%.
[0065] In some embodiments, the solid electrolyte material may be selected from the following: sulfide electrolyte, halide electrolyte, oxide electrolyte, polymer electrolyte, and any one or a combination of at least two of the above materials may be selected as the solid electrolyte in the electrode material layer 2 and the edge coating structure 3. The above solid electrolyte material is easy to obtain and has low cost, and when added to the electrode material layer 2, the electrode material layer 2 can have higher conductivity and lower internal resistance.
[0066] Exemplarily, sulfide electrolytes include LPSCl (lithium phosphorus sulfur chloride), LGPS (lithium germanium phosphorus sulfur solid electrolyte) and their derivatives; halide electrolytes include Li3YCl6, Li3InCl6 and their derivatives; oxide electrolytes include LLZO (lithium lanthanum zirconium oxide), LATP (lithium aluminum titanium phosphate), LLTO (lithium lanthanum titanate) and their derivatives.
[0067] In this embodiment, the type of solid electrolyte in the side coating structure 3 is the same as the type of solid electrolyte in the electrode material layer 2, so as to further improve the similarity between the material components of the side coating structure 3 and the material components of the electrode material layer 2. In the process of laminating the electrolyte sheet 130 and the electrode sheet 10, it can be further ensured that the thickness reduction amount of the side coating structure 3 and the electrode material layer 2 per unit time is almost the same, thereby ensuring that no cracks are generated on the electrolyte sheet 130 and the current collector 1. The thickness reduction amount of the above-mentioned side coating structure 3 refers to the difference between the thickness of the side coating structure 3 at two moments before and after, and the thickness reduction amount of the electrode material layer 2 refers to the difference between the thickness of the electrode material layer 2 at two moments before and after.
[0068] In some embodiments, the material components of the edge coating structure 3 also include insulating oxides and adhesives. If the edge coating structure 3 is conductive, when microcracks are generated in the edge area of the electrolyte sheet 130, it may cause a short circuit between the electrode material layer 2 of the positive electrode sheet and the electrode material layer 2 of the negative electrode sheet through the conductive contact of the edge coating structure 3. The presence of insulating oxides can make the edge coating structure 3 have certain insulating properties to avoid short circuits between the positive electrode sheet and the negative electrode sheet. The presence of adhesives can make the edge coating structure 3 and any of the three, the current collector 1, the electrode material layer 2 and the electrolyte sheet 130, connected to the other two by bonding, ensuring the stability of the edge coating structure 3 and preventing it from falling off.
[0069] In some embodiments, the mass of the insulating oxide in the edge coating structure 3 accounts for a percentage of the total mass of the edge coating structure 3, c. Wherein c is greater than or equal to 65% and less than or equal to 90%, so that the edge coating structure 3 has good insulation performance. For ease of description, "the mass of the insulating oxide in the edge coating structure 3 accounts for a percentage of the total mass of the edge coating structure 3" is referred to as "the mass proportion of the insulating oxide in the edge coating structure 3".
[0070] Exemplarily, the mass proportion c of the insulating oxide in the edge coating structure 3 is 65%, 66.5%, 70%, 73%, 75%, 76.2%, 78.6%, 80%, 82.7%, 85%, 88.3%, 90%, etc.
[0071] The mass percentage of the adhesive in the edge-coating structure 3 to the total mass of the edge-coating structure 3 is d. Among them, d is greater than or equal to 1% and less than or equal to 5%. Adding an adhesive with a mass percentage of 1% to 5% to the edge-coating structure 3 can ensure that the edge-coating structure 3 and the current collector 1, the edge-coating structure 3 and the electrode material layer 2, and the edge-coating structure 3 and the electrolyte sheet 130 are firmly bonded. Moreover, since the mass percentage of the adhesive is less than or equal to 5%, it will not lead to a decrease in the mass percentage of the solid electrolyte and the mass percentage of the insulating oxide in the edge-coating structure 3. For the sake of ease of description, the "mass percentage of the adhesive in the edge-coating structure 3 to the total mass of the edge-coating structure 3" is referred to as the "mass percentage of the adhesive in the edge-coating structure 3".
[0072] Exemplarily, the mass proportion d of the adhesive in the edge coating structure 3 is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0073] In some embodiments, the optional range of insulating oxide materials includes: aluminum oxide, silicon oxide, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, aluminum oxide homologues, silicon oxide homologues, lithium aluminum titanium phosphate homologues, lithium lanthanum zirconium oxide homologues. Any one of the above materials or a combination of at least two of them can be selected as the insulating oxide in the edge coating structure 3. The above insulating oxide materials are easy to obtain and low in cost, and have good insulating properties.
[0074] In some embodiments, the optional range of adhesive materials includes: polyisobutylene, hydrogenated nitrile rubber, nitrile rubber, hydrogenated styrene-butadiene block copolymer, derivatives of polyisobutylene, derivatives of hydrogenated nitrile rubber, derivatives of nitrile rubber, derivatives of hydrogenated styrene-butadiene block copolymer. Any one of the above materials or a combination of at least two of them can be selected as the adhesive in the edge coating structure 3. The above adhesive materials are easy to obtain, low in cost, and have high bonding performance.
[0075] Exemplarily, the edge coating structure 3 is attached to the circumference of the electrode material layer 2 by spraying. First, a slurry of the edge coating structure 3 is prepared, and then the prepared slurry is sprayed on the four sides of the electrode material layer 2 by a spraying device. During spraying, a mask is used to cover the electrode material layer 2, wherein the mask has a masking area and a hollow area, the masking area is consistent with the size of the electrode material layer 2, and completely covers the electrode material layer 2 to prevent the slurry from being sprayed on the electrode material layer 2, and the size of the hollow area is consistent with the size of the support area 20 to reveal the support area 20 around the electrode material layer 2. After the mask is arranged, the spraying equipment sprays the edge coating structure 3 slurry onto the current collector 1 through the hollow area of the mask. During spraying, the thickness of the edge coating structure 3 can be controlled to be consistent with the thickness of the electrode material layer 2 by controlling the output of the spraying equipment per unit time and the spraying time. The sprayed slurry falls into the space enclosed by the inner wall of the hollow area and the edge of the electrode material layer 2 and does not exceed the edge of the current collector 1 , so that the edge of the sprayed edge coating structure 3 is flush with the edge of the positive electrode current collector 111 .
[0076] Exemplarily, the spraying equipment is an ultrasonic atomization spraying equipment, which makes the spraying more uniform, improves the density of the edge coating structure 3 formed by spraying, and ensures the strength of the edge coating structure 3.
[0077] The step of preparing the slurry of the edge coating structure 3 includes: adding insulating oxide powder and solid electrolyte to a mixer, and stirring and mixing them at high speed until they are evenly mixed. Then, the mixed materials are added to a double planetary mixer, a binder is added, and an appropriate amount of solvent is added to prepare a slurry with suitable viscosity and stability. The above solvents include non-polar solvents such as p-xylene, anisole, tetralin, butyl butyrate, isobutyl isobutyrate, etc.
[0078] The present embodiment also provides a battery cell 100, including a positive electrode sheet 110, a negative electrode sheet 120, and an electrolyte sheet 130, wherein the electrolyte sheet 130 is located between the positive electrode sheet 110 and the negative electrode sheet 120, and one of the positive electrode sheet 110 and the negative electrode sheet 120 uses the electrode sheet 10 as described above. That is, the electrode sheet 10 provided in the present embodiment can be the positive electrode sheet 110 or the negative electrode sheet 120. The structures of the electrode sheet 10 and the battery cell 100 provided in the present embodiment are described below with reference to two specific implementation schemes.
[0079] The first embodiment is as Figure 4 and Figure 5 The positive electrode sheet 110 of the battery cell 100 is the electrode sheet 10 provided in the embodiment of the present application.
[0080] Specifically, the positive electrode plate 110 includes a positive electrode collector 111 and a positive electrode material layer 112. The positive electrode material layer 112 may be a slice layer, which is formed by cutting and coated on the positive electrode collector 111; the positive electrode material layer 112 may also be a coating coated on the positive electrode collector 111. The positive electrode collector 111 and the positive electrode material layer 112 are both rectangular, and the length and width of the positive electrode material layer 112 are respectively smaller than the length and width of the positive electrode collector 111. The four edges of the positive electrode material layer 112 are spaced apart from the edges of the positive electrode collector 111, so that an annular support area 20 is formed between the edge of the positive electrode material layer 112 and the edge of the positive electrode collector 111. Correspondingly, the edge coating structure 3 is annular and is arranged outside the positive electrode material layer 112. Figure 4 As shown, a positive electrode tab 1110 is disposed on the positive electrode current collector 111 .
[0081] See also Figure 5 The negative electrode sheet 120 includes a negative electrode current collector 121 and a negative electrode material layer 122 . The negative electrode material layer 122 may be a coating formed by coating a slurry of negative electrode active material on the negative electrode current collector 121 , or may be a slice layer formed by cutting.
[0082] The electrolyte sheet 130 is stacked on the side of the positive electrode material layer 112 facing away from the positive electrode current collector 111, and the negative electrode sheet 120 is stacked on the side of the electrolyte sheet 130 facing away from the positive electrode sheet 110, and the electrolyte sheet 130 is located between the negative electrode material layer 122 and the positive electrode material layer 112. In some embodiments, the edge of the negative electrode current collector 121, the edge of the negative electrode material layer 122, the edge of the electrolyte sheet 130, the edge of the edge coating structure 3, and the edge of the positive electrode current collector 111 are all flush, such as Figure 5 After the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 are stacked, pressure is applied to make the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 fit closely together. During the pressure application process, the positive electrode material layer 112 and the side coating structure 3 have highly similar material components, so the thickness reduction per unit time is almost the same, and the thickness of the two is approximately equal at any time, that is, the positive electrode material layer 112 and the side coating structure 3 are almost flush with the side contacting the positive electrode current collector 111, and the side contacting the electrolyte sheet 130 is also almost flush, which can ensure that the electrolyte sheet 130, the positive electrode current collector 111, the negative electrode current collector 121 and the negative electrode material layer 122 will not crack during the stacking process.
[0083] like Figure 5 The battery cell 100 shown in the figure has a positive electrode material layer 112 and an edge coating structure 3 disposed on both sides of the positive electrode current collector 111. Correspondingly, the battery cell 100 includes two electrolyte sheets 130 and two negative electrode sheets 120. The battery cell 100 includes a negative electrode sheet 120, an electrolyte sheet 130, a positive electrode sheet 110, an electrolyte sheet 130, and a negative electrode sheet 120 from top to bottom.
[0084] The second embodiment is as Figure 6 and Figure 7 The negative electrode sheet 120 of the battery cell 100 is the electrode sheet 10 provided in the embodiment of the present application.
[0085] Specifically, the negative electrode sheet 120 includes a negative electrode current collector 121 and a negative electrode material layer 122. The negative electrode material layer 122 can be a coating formed by coating a slurry of negative electrode active materials on the negative electrode current collector 121, or a slice layer formed by cutting. The negative electrode current collector 121 and the negative electrode material layer 122 are both rectangular, and the length and width of the negative electrode material layer 122 are respectively smaller than the length and width of the negative electrode current collector 121. The four edges of the negative electrode material layer 122 are spaced from the edges of the negative electrode current collector 121, so that an annular support area 20 is formed between the edge of the negative electrode material layer 122 and the edge of the negative electrode current collector 121. Accordingly, the edge coating structure 3 is annular and is arranged outside the negative electrode material layer 122. Figure 6 As shown, a negative electrode tab 1210 is disposed on the negative electrode current collector 121 .
[0086] See also Figure 7 The positive electrode sheet 110 includes a positive electrode current collector 111 and a positive electrode material layer 112. The positive electrode material layer 112 may be a slice layer formed by cutting and covered on the positive electrode current collector 111; the positive electrode material layer 112 may also be a coating coated on the positive electrode current collector 111.
[0087] The electrolyte sheet 130 is stacked on the side of the negative electrode material layer 122 facing away from the negative electrode current collector 121, and the positive electrode sheet 110 is stacked on the side of the electrolyte sheet 130 facing away from the negative electrode current collector 120, and the electrolyte sheet 130 is located between the negative electrode material layer 122 and the positive electrode material layer 112. In some embodiments, the edge of the positive electrode current collector 111, the edge of the positive electrode material layer 112, the edge of the electrolyte sheet 130, the edge of the edge coating structure 3, and the edge of the negative electrode current collector 121 are all flush, such as Figure 7 After the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 are stacked, pressure is applied to make the negative electrode sheet 120, the electrolyte sheet 130 and the positive electrode sheet 110 fit closely together. During the pressure application process, the negative electrode material layer 122 and the side coating structure 3 have highly similar material components, so the thickness reduction per unit time is almost the same, and the thickness of the two is approximately equal at any time, that is, the side of the negative electrode material layer 122 and the side coating structure 3 that are in contact with the negative electrode current collector 121 are almost flush, and the side of the two that are in contact with the electrolyte sheet 130 are also almost flush, which can ensure that the electrolyte sheet 130, the negative electrode current collector 121, the positive electrode current collector 111 and the positive electrode material layer 112 will not crack during the stacking process.
[0088] like Figure 7 The battery cell 100 shown in the figure has negative electrode material layers 122 and edge coating structures 3 disposed on both sides of the negative electrode current collector 121. Correspondingly, the battery cell 100 includes two electrolyte sheets 130 and two positive electrode sheets 110. The battery cell 100 includes a positive electrode sheet 110, an electrolyte sheet 130, a negative electrode sheet 120, an electrolyte sheet 130, and a positive electrode sheet 110 from top to bottom.
[0089] like Figure 8 and Fig. 9 As shown, this embodiment also provides a battery, including a packaging structure 200 and at least one battery cell 100 as described above, wherein the battery cell 100 is located in the packaging structure 200. The battery having the battery cell 100 has a high yield rate because cracks are less likely to occur on the electrolyte sheet 130 and the current collector 1. Furthermore, when the edge coating structure 3 contains an adhesive, the electrolyte sheet 130 is not easily separated from the electrode sheet 10 after long-term use of the battery, resulting in failure of the originally tight fit, thereby effectively preventing the increase of the interface impedance.
[0090] Exemplarily, a plurality of battery cells 100 are provided along the thickness direction, such as 2 to 50. In two adjacent battery cells 100, the positive electrode tab 1110 of one and the negative electrode tab 1210 of the other are conductively connected through a connecting sheet 300. A heat conducting layer 400 is provided between two adjacent battery cells 100 to facilitate achieving temperature consistency of multiple battery cells 100 inside the battery.
[0091] See also Figure 8 The positive electrode tab 1110 of the top battery cell 100 is electrically connected to the battery positive electrode tab 500, and the negative electrode tab 1210 of the bottom battery cell 100 is electrically connected to the battery negative electrode tab 600. Both the battery positive electrode tab 500 and the battery negative electrode tab 600 are partially disposed outside the packaging structure 200.
[0092] Further, the packaging structure 200 may include an aluminum-plastic film structure, wherein the aluminum-plastic film structure includes an upper aluminum-plastic film and a lower aluminum-plastic film arranged opposite to each other, the battery cell 100 is placed between the upper aluminum-plastic film and the lower aluminum-plastic film, and the edge region of the upper aluminum-plastic film and the edge region of the lower aluminum-plastic film are stacked and bonded together, so that the upper aluminum-plastic film and the lower aluminum-plastic film seal and wrap the battery cell 100. The electrode sheet 10 provided in the present application is described in detail below in the form of a specific embodiment.
[0093] Example 1
[0094] The present embodiment provides a battery, the battery cell of which includes an electrode sheet 10 and an electrolyte sheet 130, the electrode sheet 10 and the electrolyte sheet 130 are stacked, and the electrode sheet 10 includes a current collector 1, an electrode material layer 2 and a side coating structure 3. The electrode material layer 2 is arranged on the current collector 1 and falls in the area where the current collector 1 is located, the outer contour of the area where the electrode material layer 2 is located is at least partially spaced from the outer contour of the area where the current collector 1 is located, and a support area 20 is formed between the outer contour of the area where the electrode material layer 2 is located and the outer contour of the area where the current collector 1 is located. The side coating structure 3 is arranged in the support area 20; the material components of the electrode material layer 2 and the material components of the side coating structure 3 both include solid electrolytes.
[0095] Among them, the percentage of the mass of each material in the electrode material layer 2 to the total mass of the electrode material layer 2 is: electrode material (positive electrode material or negative electrode material) 85%, solid electrolyte 12% (ie a is 12%), adhesive 1.5%, conductive agent 1.5%.
[0096] The percentage of the mass of each material in the edge coating structure 3 to the total mass of the edge coating structure 3 is: the mass proportion c of the insulating oxide is 86%, the mass proportion b of the solid electrolyte is 12%, and the mass proportion d of the adhesive is 2%. In this embodiment, the mass proportion b of the solid electrolyte in the edge coating structure 3 is the same as the mass proportion a of the solid electrolyte in the electrode material layer 2.
[0097] An electrolyte sheet 130 is stacked on the side of the electrode material layer 2 facing away from the current collector 1 , so that a portion of the electrolyte sheet 130 falls on the electrode material layer 2 and another portion falls on the edge coating structure 3 .
[0098] The electrolyte sheet 130 and the electrode sheet 10 are pressurized to a pressure of 400 MPa, and the pressure is maintained for 10 minutes.
[0099] Example 2
[0100] This embodiment provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of the embodiment 1 in that:
[0101] The mass proportions of the materials in the side coating structure 3 are as follows: the mass proportion c of the insulating oxide is 88.5%, the mass proportion b of the solid electrolyte is 10%, and the mass proportion d of the adhesive is 1.5%. In this embodiment, the mass proportion b of the solid electrolyte in the side coating structure 3 is 2% different from the mass proportion a of the solid electrolyte in the electrode material layer 2 in Example 1.
[0102] Example 3
[0103] This embodiment provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of the embodiment 1 in that:
[0104] The percentage of the mass of each material in the electrode material layer 2 to the total mass of the electrode material layer 2 is: electrode material (positive electrode material or negative electrode material) 77%, solid electrolyte 20% (ie a is 20%), adhesive 1.5%, conductive agent 1.5%.
[0105] The mass proportions of the materials in the edge coating structure 3 are as follows: the mass proportion c of the insulating oxide is 78.5%, the mass proportion b of the solid electrolyte is 20%, and the mass proportion d of the adhesive is 1.5%.
[0106] In this embodiment, the mass proportion b of the solid electrolyte in the edge coating structure 3 is the same as the mass proportion a of the solid electrolyte in the electrode material layer 2 .
[0107] Example 4
[0108] This embodiment provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of the embodiment 3 in that:
[0109] The mass proportions of the materials in the side coating structure 3 are as follows: the mass proportion c of the insulating oxide is 75.5%, the mass proportion b of the solid electrolyte is 23%, and the mass proportion d of the adhesive is 1.5%. In this embodiment, the mass proportion b of the solid electrolyte in the side coating structure 3 is 3% different from the mass proportion a of the solid electrolyte in the electrode material layer 2 in Example 1.
[0110] Example 5
[0111] This embodiment provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of the embodiment 1 in that:
[0112] The percentage of the mass of each material in the electrode material layer 2 to the total mass of the electrode material layer 2 is: electrode material (positive electrode material or negative electrode material) 67.5%, solid electrolyte 30% (ie a is 30%), adhesive 1%, conductive agent 1.5%.
[0113] The mass proportions of the materials in the edge coating structure 3 are as follows: the mass proportion c of the insulating oxide is 68.5%, the mass proportion b of the solid electrolyte is 30%, and the mass proportion d of the adhesive is 1.5%.
[0114] In this embodiment, the mass proportion b of the solid electrolyte in the edge coating structure 3 is the same as the mass proportion a of the solid electrolyte in the electrode material layer 2 .
[0115] Example 6
[0116] This embodiment provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of the embodiment 5 in that:
[0117] The mass proportions of the materials in the side coating structure 3 are as follows: the mass proportion c of the insulating oxide is 72%, the mass proportion b of the solid electrolyte is 26%, and the mass proportion d of the adhesive is 2%. In this embodiment, the mass proportion b of the solid electrolyte in the side coating structure 3 differs by 4% from the mass proportion a of the solid electrolyte in the electrode material layer 2 in Example 1.
[0118] Example 7
[0119] The difference between this embodiment and embodiment 1 is that the pressure when the electrolyte sheet 130 and the electrode sheet 10 are pressurized is 400 MPa, and the pressure is maintained for 40 minutes.
[0120] Example 8
[0121] The difference between this embodiment and embodiment 1 is that the pressure when the electrolyte sheet 130 and the electrode sheet 10 are pressurized is 300 MPa, and the pressure is maintained for 40 minutes.
[0122] Comparative Example 1
[0123] This comparative example provides a battery, and the electrode sheet 10 of the battery cell of the battery is different from that of Example 1 in that:
[0124] The mass proportions of the materials in the edge coating structure 3 are as follows: the mass of the insulating oxide accounts for 98.5% of the total mass of the edge coating structure 3 , and the mass of the adhesive accounts for 1.5% of the total mass of the edge coating structure 3 .
[0125] The side coating structure 3 in Comparative Example 1 does not contain a solid electrolyte.
[0126] The electrolyte sheet 130 is stacked on the electrode material layer 2 of the electrode sheet 10 provided in the above-mentioned embodiments 1 to 8 and comparative example 1, and pressurized according to the set pressure in each embodiment and comparative example. After the pressure is maintained for a set time, the cracks on the electrolyte sheet 130 and the current collector 1 are observed using an electron microscope as shown in the following table:
[0127]
[0128]
[0129] It can be seen from the above table that compared with Comparative Example 1, the side coating structure 3 and the electrode material layer 2 in Examples 1 to 8 both contain solid electrolyte materials. In the process of stacking the electrolyte sheet 130 and the electrode sheet 10, the number of cracks generated on the electrolyte sheet 130 and the current collector 1 is significantly reduced or even free of cracks. Moreover, the closer the mass proportion b of the solid electrolyte in the side coating structure 3 is to the mass proportion a of the solid electrolyte in the electrode material layer 2, the fewer cracks are generated. The larger the mass proportion b of the solid electrolyte in the side coating structure 3 and the mass proportion a of the solid electrolyte in the electrode material layer 2, the more cracks are generated on the electrolyte sheet 130 and the current collector 1. The smaller the mass proportion d of the adhesive in the side coating structure 3, the more cracks are generated on the electrolyte sheet 130 and the current collector 1.
[0130] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those of ordinary skill in the art, various obvious changes, readjustments, and substitutions can be made without departing from the protection scope of the present application. It is not necessary and impossible to list all implementation methods exhaustively here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present application shall be included in the protection scope of the claims of the present application.
Claims
1. A battery, characterized in that The invention comprises at least one battery cell (100), wherein the battery cell (100) comprises an electrode sheet (10) and an electrolyte sheet (130), wherein the electrode sheet (10) and the electrolyte sheet (130) are stacked and arranged, and the electrode sheet (10) comprises: current collector(1); An electrode material layer (2) is disposed on the current collector (1) and falls within the region where the current collector (1) is located, and the outer contour of the region where the electrode material layer (2) is located is at least partially spaced from the outer contour of the region where the current collector (1) is located, so that a support region (20) is formed between the outer contour of the region where the electrode material layer (2) is located and the outer contour of the region where the current collector (1) is located; A side coating structure (3) is provided in the support area (20); the electrolyte sheet (130) covers at least a portion of the electrode material layer (2) and at least a portion of the side coating structure (3); The material components of the edge coating structure (3) include a solid electrolyte.
2. The battery according to claim 1, characterized in that The material components of the electrode material layer (2) include a solid electrolyte.
3. The battery according to claim 2, characterized in that The mass of the solid electrolyte in the electrode material layer (2) accounts for a percentage of the total mass of the electrode material layer (2), and the mass of the solid electrolyte in the edge coating structure (3) accounts for b percentage of the total mass of the edge coating structure (3); The absolute value of the difference between a and b is greater than or equal to 0 and less than or equal to 5%.
4. The battery according to claim 2, characterized in that The percentage of the mass of the solid electrolyte in the electrode material layer (2) to the total mass of the electrode material layer (2) is a, and a is greater than or equal to 5% and less than or equal to 35%.
5. The battery according to claim 1, characterized in that The percentage of the mass of the solid electrolyte in the edge coating structure (3) to the total mass of the edge coating structure (3) is b; b is greater than or equal to 5% and less than or equal to 35%.
6. The battery according to any one of claims 1 to 5, characterized in that: The material components of the edge coating structure (3) also include insulating oxides and adhesives.
7. The battery according to claim 6, characterized in that The percentage of the mass of the insulating oxide in the edge coating structure (3) to the total mass of the edge coating structure (3) is c, and c is greater than or equal to 65% and less than or equal to 90%.
8. The battery according to claim 6, characterized in that The percentage of the mass of the adhesive in the edge coating structure (3) to the total mass of the edge coating structure (3) is d; d is greater than or equal to 1% and less than or equal to 5%.
9. The battery according to claim 6, characterized in that The insulating oxide includes any one of aluminum oxide, silicon oxide, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, aluminum oxide homologues, silicon oxide homologues, lithium aluminum titanium phosphate homologues, and lithium lanthanum zirconium oxide homologues, or a combination of at least two thereof.
10. The battery according to claim 6, characterized in that The adhesive includes any one or a combination of at least two of polyisobutylene, hydrogenated nitrile rubber, nitrile rubber, hydrogenated styrene-butadiene block copolymer, derivatives of polyisobutylene, derivatives of hydrogenated nitrile rubber, derivatives of nitrile rubber, and derivatives of hydrogenated styrene-butadiene block copolymer.
11. The battery according to any one of claims 1 to 5, characterized in that: The type of the solid electrolyte in the edge coating structure (3) is the same as the type of the solid electrolyte in the electrode material layer (2).
Citation Information
Patent Citations
Anti-short-circuit positive plate and anti-short-circuit solid-state battery comprising same
CN117117206A
All-solid-state rechargeable battery, stacked rechargeable all-solid-state battery, and manufacturing method thereof
US20230344083A1
Cited By
Battery
WO2026021610A1